Answer: The required simplified answer in standard form is [tex]8y^6-88y^5-6y^3+61y^2+55y.[/tex]
Step-by-step explanation: We are given to multiply the following polynomials and write the answer is standard form :
[tex]M=(-6y+8y^4-5)(y^2-11y)~~~~~~~~~~~~~~~~~~~~~~~~~~~~(i)[/tex]
To multiply the given polynomials, we need to multiply each term of one polynomial to each term of the other polynomial.
From (i), we have
[tex]M\\\\=(-6y+8y^4-5)(y^2-11y)\\\\=y^2(-6y+8y^4-5)-11y(-6y+8y^4-5)\\\\=-6y^3+8y^6-5y^2+66y^2-88y^5+55y\\\\=8y^6-88y^5-6y^3+61y^2+55y.[/tex]
Thus, the required simplified answer in standard form is [tex]8y^6-88y^5-6y^3+61y^2+55y.[/tex]